The Role of Digital Marketing as a Strategy in Improving Wonosobo MSME Product Marketing - Rachmawatie, Dessy (Jurnal Pemberdayaan Ekonomi dan Masyarakat, 2024)
T Karangsari Village, Sapuran District, Kaabupaten Wonosobo is one of the villages in Wonosobo Regency that has the potential of a Tourism Village. With the increasing number of tourist visitors, it will increase the potential income for local village communities. Wonosobo Regency typical products have been widely known by the public, but since the occurrence of Covid 19 has caused a lack of tourist visitors visiting tourist sites in Karangsari Village, Sapuran District, Wonosobo Regency. This condition also has an impact on the quiet sales turnover of MSME products, especially in Karangsari Village, Sapuran District, Wonosobo Regency. One of the contributing factors is caused by the marketing model that is still carried out traditionally, so that when the Covid 19 pandemic occurred, it was very difficult for local entrepreneurs to survive running their businesses. Digital marketing is a business strategy that can be used when there are government policies related to social restrictions of the community. The purpose of this community service is to develop products and increase online sales, in order to increase marketing reach. The methods carried out are by: (1) providing training and socialization about the concept of Digital Marketing and its usefulness in business strategies, (2) utilizing digital marketing through social media.